Unveiling Internet Network Quality: A Wireshark Analysis at SMKN 2 Rejang Lebong - Joshi, Jericko Vivaldo; Wibowo, Sastya Hendri; Toyib, Rozali (UNIVED Press, 2023)
Quality of Service (QoS) analysis is crucial for ensuring high-quality network performance. This study, conducted at SMKN 2 Rejang Lebong, utilizes Wireshark version 2.0.4 to analyze QoS parameters such as throughput, delay, jitter, and packet loss. The research employs a quantitative methodology, collecting data through questionnaires and employing descriptive statistics using SPSS version 20. The findings reveal that the QoS index for the Office Building and Teachers' Room falls within the 'Satisfactory' category with values of 3.06 and 3.26, respectively. However, the LAB Room scores a lower QoS index of 2.45, categorized as 'Unsatisfactory.' Overall, the internet network quality at SMKN 2 Rejang Lebong aligns with TIPHON standards, classifying as 'Less Satisfactory' with an average score of 2.92.